Business law and the regulation of business - Mann, Richard A. (Thomson/South-Western West, 2005)
This book is extremely thorough. Very intimidating at first but has helped me tremendously with my class. Would highly recommend if taking a Business Law class, covers materials in depth as well as gives examples for of each law and terms for those of US who need to see or hear an example before actually undeerstanding what some things mean....